Strategy Of The Local Government In Developing Tourism Sector To Increase The Local Revenue(PAD) (Study in Culture, Tourism, Youth and Sport Institution of Tulungagung) - Rismianto, Defid Dwi (Jurnal Administrasi Publik, 2013)
Abstract: Strategy Of The Local Government In Developing Tourism Sector To Increase the Local Revenue. As one of the tourist destinations in East Java, Tulungagung has many interesting sights to be developed and has great potential in improving the local revenue. Thus the purpose of this study, researchers wanted to analyze the government's strategy Tulungagung in optimizing the tourism sector to increase local revenue (PAD).This research is using qualitative methods and trends deskripstif approach using SWOT analysis. SWOT analysis is the analysis of the internal and external conditions for an organization which would then be used as a basis for designing strategies and work programs. While Data was collected through interviews and documentation Based on the analysis of research, tourism development strategy in an attempt Tulungagung DISBUDPARPORA as the pace of development of tourism potential contained in Tulungagung. Potential can be seen from the number of natural and cultural tourism, as well as the amount of as much as 19 tourism object (ODTW) nature and cultural tourism as much as 48 tourism object (ODTW). Of various ODTW only a few that can be optimized as a local revenue. In developing the tourism potential, the strategy taken by DISBUDPARPORA include development of tourism destinations, Tourism Infrastructure Development, to increase the capacity of Human Resources (HR), the development of cooperation with stakeholders in Tourism, Marketing and Promotion of tourism and the Increasing Role of Actors Tourism. From the various efforts to develop the tourism sector's contribution in improving the local Revenue Tulungagung until the end of 2012 is still lacking, but that number fluctuates new in the range of 1%. This can be seen from the total tourism revenue is still relatively small compared to the total revenue Tulungagung until 2012. Based on the analysis and the problems that arise, the researchers gave suggestions include development of tourism Tulungagung using SWOT analysis conducted for tourism development strategy. Keywords: Strategy, Tourism Development, SWOT, Local Revenue(PAD).